2015
DOI: 10.1021/jacs.5b11230
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer Stabilization of Late Transition Metal Oxide Nanoparticles on a Layered Niobate Support

Abstract: The interfacial interactions between late transition metal/metal oxide nanoparticles and oxide supports impact catalysts’ activity and stability. Here, we report the use of isothermal titration calorimetry (ITC), electron microscopy and density functional theory (DFT) to explore periodic trends in the heats of nanoparticle-support interactions for late transition metal and metal oxide nanoparticles on layered niobate and silicate supports. Data for Co(OH)2, hydroxyiridate-capped IrOx.nH2O, Ni(OH)2, CuO, and Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 48 publications
10
60
2
Order By: Relevance
“…5 nm are observed almost entirely coating the VO 2 nanocrystals (which at this concentration are crystallized in the M 1 phase) as depicted in Figure f. The dispersion of nanocrystalline Ir metal on the VO 2 surfaces is suggestive of strong interfacial interactions and likely derives from d‐acid/base interactions as originally suggested by Brewer wherein early (V) and late (Ir) transition metals undergo strong orbital mixing of d‐states yielding homogeneously dispersed clusters on the oxide surface …”
Section: Resultssupporting
confidence: 59%
“…5 nm are observed almost entirely coating the VO 2 nanocrystals (which at this concentration are crystallized in the M 1 phase) as depicted in Figure f. The dispersion of nanocrystalline Ir metal on the VO 2 surfaces is suggestive of strong interfacial interactions and likely derives from d‐acid/base interactions as originally suggested by Brewer wherein early (V) and late (Ir) transition metals undergo strong orbital mixing of d‐states yielding homogeneously dispersed clusters on the oxide surface …”
Section: Resultssupporting
confidence: 59%
“…Campbell et al. demonstrated that the oxide formation energy of the metal adatom can be used to predict the adsorption energy of support oxides, and the tendency has been validated experimentally and theoretically . Besides, the metal atom adsorption also depends on the capability of the support oxide to accept electrons to release oxygen atoms, calculated as reduction energy, O'Connor et al.…”
Section: Strategy To Improve Co Oxidation By Controlling the Interactmentioning
confidence: 99%
“…[1][2][3][4][5] Especially, tricobalt tetraoxide (Co 3 O 4 ), a mixed-valence transition metal oxide with spinel crystal structure, is regarded as one of the most promising p-type semiconducting materials for industrial and scienti c applications such as heterogeneous catalysts, [6][7][8][9][10][11][12] solid-state sensors, [13][14][15] magnetic materials, 16,17) and lithium ion rechargeable batteries. [18][19][20][21] Up to date, various types of preparation methods have been developed for the preparation of Co 3 O 4 by thermal decomposition, [6][7][8]20,22,23) chemical spray pyrolysis, 24) spattering, 25) and sol-gel process.…”
Section: Introductionmentioning
confidence: 99%